IMPLEMENTASI TEORI PSIKOLOGI PERKEMBANGAN DALAM PENGEMBANGAN METODE PEMBELAJARAN DI MADRASAH - Muhammad Tambrin (ADIBA : JOURNAL OF EDUCATION, 2022)
This paper seeks to find out how the implementation of developmental theory in the development of learning methods in madrasas is. The learning method is the method used to deliver the subject matter to students. For this reason, varied, effective and efficient methods are needed so that the desired goals are achieved. Good learning methods will make students more motivated to achieve learning goals. Developmental psychology theories can be used in developing how learning should be carried out in madrasas. Each developmental psychology theory has its advantages and disadvantages. There is no single theory that perfectly explains human development. These theories are like a puzzle that completes each other. Incorporative eclectic learning methods can take the advantages of each of these theories so as to create a complete blend.